BRAF inhibition: Bridge or boost to T cell therapy? - Goff, Stephanie L. (Clin Cancer Res, 2019)
The concept of treatment-refractory disease has evolved as checkpoint modulation has changed the therapeutic landscape for patients with metastatic melanoma. Developing meaningful salvage strategies will involve the exploration of combination therapies and new immunotherapeutics, including adoptive transfer of tumor infiltrating lymphocytes or other T-cell based therapy.